Does screening for prostate cancer improve cancer‐specific mortality in Asian men? Real‐world data in Yokosuka City 15 years after introducing PSA‐based population screening. Issue 11 (20th May 2020) - Tabei, Tadashi; Taguri, Masataka; Sakai, Naoki; Koh, Hideshige; Yosida, Minoru; Fujikawa, Atsushi; Nirei, Takuma; Tsutsumi, Sohgo; Ito, Hiroki; Furuhata, Souichi; Kawahara, Takashi; Miyoshi, Yasuhide; et al.
Abstract: Background: Studies of prostate‐specific antigen (PSA)‐based population screening have been conducted in western countries, but there is little data in Asian populations. The objective of this study was to determine the efficacy of PSA screening in Asian men using real‐world data over a period of 15 years after introducing population screening in Yokosuka City, Japan. Methods: We investigated patients with pathologically diagnosed prostate cancer at four hospitals and two clinics across the Yokosuka area (Miura peninsula) between April 2001 and March 2015. Patients were divided into two groups; the S group consisted of those diagnosed by PSA‐based population screening in Yokosuka City and the NS group consisted of those diagnosed by methods other than screening. Cancer‐specific survival (CSS) and overall survival (OS) rates were calculated using the Kaplan‐Meier method with the log‐rank test to compare survival between the two groups. Clinical and pathological factors for cancer‐specific mortality were assessed with Cox regression analyses to calculate the hazard ratio (HR) and 95% confidence interval (CI). Results: A total of 3094 patients had been diagnosed with prostate cancer over the 15‐year period. The median follow‐up period was 77 months. The S group and the NS group consisted of 977 and 2117 patients, respectively. Patients in the S group were younger (age: 71 years vs 73 years, P < .001) and had a lower Charlson comorbidity index (CCI) with favorable oncological factors, such as lower initial PSA, Gleason score (GS), and risk category. Kaplan‐Meier curves for OS and CSS revealed significant differences between the two groups (OS: P < .001, CSS: P < .001). Analysis with Cox proportional hazards model indicated the NS group (HR: 1.584, 95% CI, 1.065‐2.356, P = .023), a CCI > 4 (HR: 1.552, 95% CI, 1.136‐2.120, P = .006), a GS ≥ 8 (HR: 4.869, 95% CI, 2.631‐9.001, P < .001), and nonlocalized cancer (locally advanced; HR: 2.632, 95% CI, 1.676‐4.133, P < .001, advanced; HR: 9.468, 95% CI, 6.279‐14.278, P < .001) as independent risk factors for cancer‐specific mortality. Conclusions: PSA‐based population screening of prostate cancer might be useful in the Japanese population.